Upaya Meningkatkan Keterampilan Membaca Anak Kelas 1 SD Muhammadiyah 26 dengan Metode Quantum Learning dalam Pembelajaran Daring - Finna Ristiana; Fitroh Setyo Putro Pribowo; Kunti Dian Ayu Afiani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The corona virus pandemic in Indonesia has greatly affected the learning education system. People are being forced to switch to online learning. Many obstacles in the process of students absorbing the knowledge, especially kids who have not been able to concentrate on a long time facing the screen because their age is happy to move actively. The purpose of this study is how to improve students' reading skills through the quantum teaching method while studying online. This classroom action research was held at SD Muhammadiyah 26 Surabaya with 27 students in class 1C. Data collection method is using classroom action research on online learning through meetings using the Teams. The implementation of cycle I the average value of the students' reading ability 51,85% students do not receive standart value. After cyclus II the average value contains 82% students succed and only 18% students don’t receive standart value and. Based on the data analysis, the use of the quantum teaching method can improve reading skills in IC class students of SD Muhammadiyah 26 Surabaya because the atmosphere when reading is designed more fun and memorable for children and reading activities will increase the brain's working power and improve their skill reading.